Hydrogen Production During Ethylene Glycol Photoreactions Over Ag-Pd/TiO2 at Different Partial Pressures of Oxygen - Wahab, Ahmed Khaja; Nadeem, Mohammad Amtiaz; Idriss, Hicham (Frontiers in Chemistry, 2019)
The reaction of ethylene glycol has been studied over Ag - Pd/TiO2 (anatase) under photo-irradiation while monitoring the reaction products (in the gas and liquid phases) as a function of time and at different partial pressures of molecular oxygen. The catalyst contained metal particles with a mean size of about 1 nm, most likely in the form of alloy (TEM, STEM, and XPS). The complex reaction network involves hydrogen abstraction, C-C bond dissociation, de-carbonylation and water gas shift ultimately yielding hydrogen and CO2. The two main competing reactions were found to be, photo reforming and photo-oxidation. Based on our previous study, Ag presence improves the reaction rate for hydrogen production, most likely via decreasing the adsorption energy of CO when compared to pure Pd. At high ethylene glycol concentrations, the rate of hydrogen produced decreased by a factor of two while changing O2 partial pressure from 0.001 to 0.2 atm. The rate was however very sensitive to oxygen partial pressures at low ethylene glycol concentrations, decreasing by about 50 times with increasing oxygen pressures to 1 atm. The order of reaction with respect to O2 changed from near zero at high oxygen partial pressure to ½ at low partial pressure (in 0.008-0.2 atm. range). Liquid phase analysis indicated that the main reaction product was formaldehyde, where its concentration was found to be higher than that of H2 and CO2. The mass balance approaced near unity only upon the incorporation of formaldehyde and after a prolonged reaction time. This suggests that the photo-reforming reaction was not complete even at prolonged time, most likely due to kinetic limitations.